TOPIC-BASED ESP MATERIALS FOR VOCATIONAL SCHOOL - Banun Havifah Cahyo Khosiyono (Universitas Muria Kudus, 2018)
This paper aims to describe how to design topic-based ESP materials for Vocational School. ESP is an approach to language teaching whichaims to meet the needs of particular learners. Moreover, topic-based ESP materials for Vocational School should be designeddepend on the needs of the learners in relation to their future or present jobs. The topic-based ESP materials should focus on the appropriate topics and include tasks and activities that practice the target skills areas.